Minor allele frequency of myeloproliferative neoplasm mutations in the Irish blood donor population. Issue 3 (3rd February 2015) - Titmarsh, Glen J.; McKay, Gareth J.; Lawler, Mark; Anderson, Lesley A.; McMullin, Mary Frances
Abstract: Myeloproliferative neoplasms (MPNs) are rare diseases that include classic entities; polycythaemia vera, essential thrombocythaemia and primary myelofibrosis. In this short report, minor allele frequencies of common MPN mutations are compared between the Irish blood donor population and other populations of European descent using data from the Haplotype Map project. The Affymetrix array 6.0 platform was utilised identifying nine single nucleotide polymorphisms (SNPs) and six proxy SNPs. The variability of allele frequencies for MPN mutations could account for the different incidence rates seen between populations of European ancestry, giving a better understanding of the genetic predisposition to MPNs. Copyright © 2015 John Wiley & Sons, Ltd.